Elity : Velkomoravské elity z Mikulčic - Poláček, Lumír (2022)
This collective monograph provides a comprehensive interdisciplinary account of the social elites in Great Moravian Mikulčice by drawing on sources of information from history, archaeology and anthropology. The main areas of knowledge about the form and function of this important early medieval centre and the life of the elites are gradually introduced over four thematic sections and twenty-four chapters. The first section of the book describes Great Moravia from a historical point of view. The following section presents archaeological evidence and addresses Mikulčice as an island stronghold and power centre. The third section is focused on selected categories of elite material culture, especially luxury goods. The final section provides the results of bioarchaeological research into the skeletal remains of the Mikulčice population, primarily their health and physical condition